"Sorry, what did you say?" Communicating defibrillator retrieval and use in OHCA emergency calls. (November 2020) - Perera, Nirukshi; Ball, Stephen; Birnie, Tanya; Morgan, Alani; Riou, Marine; Whiteside, Austin; Perkins, Gavin D.; Bray, Janet; Fatovich, Daniel M.; Cameron, Peter; Brink, Deon; Bailey, Paul; et al.
Abstract: Background: The defibrillator prompt, which directs callers to retrieve a defibrillator during out-of-hospital cardiac arrest, is crucial to the emergency call because it can save lives. We evaluated communicative effectiveness of the prompt instated by the Medical Priority Dispatch System™ Version 13, namely: if there is a defibrillator (AED) available, send someone to get it now, and tell me when you have it . Methods: Using Conversation Analysis and descriptive statistics, we examined linguistic features of the defibrillator sequences (call-taker prompt and caller response) in 208 emergency calls where non-traumatic out-of-hospital cardiac arrest was confirmed by the emergency medical services, and they attempted resuscitation, in the first six months of 2019. Defibrillator sequence durations were measured to determine impact on time to CPR prompt. The proportion of cases where bystanders retrieved defibrillators was also assessed. Results: There was low call-taker adoption of the Medical Priority Dispatch System™ Version 13 prompt (99/208) compared to alternative prompts (86/208) or no prompt (23/208). Caller responses to the Version 13 prompt tended to be longer, more ambiguous or unrelated, and have more instances of repair (utterances to address comprehension trouble). Defibrillators were rarely brought to the scene irrespective of defibrillator prompt utilised. Conclusion: While the Version 13 prompt aims to ensure the use of an available automatic external defibrillator, its effectiveness is undermined by the three-clause composition of the prompt and exclusion of a question structure. We recommend testing of a re-phrased defibrillator prompt in order to maximise comprehension and caller action.